(untitled) (Asian Business Research, 2022)
Based on the data of the NFCS in the United States in 2012 and 2015, we measured the level of personal financial literacy and financial literacy overconfidence. By using the Ordered Probit model empirical research, we found that financial literacy and risk appetite were significantly positively correlated, but the positive correlation between financial literacy overconfidence and risk appetite were even tighter. The results of the study showed that people with higher financial literacy levels had greater willingness to take risks, but if there were overconfidence in financial literacy, their risk appetite will be greater.